Current Conveyors Variants, Applications and Hardware Implementations - Senani, Raj; Bhaskar, D. R.; Singh, A. K. (Springer International Publishing : Imprint: Springer, 2015)
This book serves as a single-source reference to Current Conveyors and their use in modern Analog Circuit Design. The authors describe the various types of current conveyors discovered over the past 45 years, details of all currently available, off-the-shelf integrated circuit current conveyors, and implementations of current conveyors using other, off-the-shelf IC building blocks. Coverage includes prominent bipolar/CMOS/Bi-CMOS architectures of current conveyors, as well as all varieties of starting from third generation current conveyors to universal current conveyors, their implementations and applications. •Describes all commercially available off-the-shelf IC current conveyors, as well as hardware implementations of current conveyors using other off-the-shelf ICs; • Describes numerous variants of current conveyors evolved over the past forty five years; • Describes a number of Bipolar/CMOS/Bi-CMOS architectures of current conveyors, along with their characteristic features; • Includes a comprehensive collection of over 400 application circuits using current conveyors; • Provides an exhaustive catalogue of current conveyor-based circuits for a variety of applications, including instrumentation amplifiers, precision rectifiers, simulated inductors, filters, sinusoidal oscillators, waveform generators, chaos generators, analog multipliers/dividers, memristive emulators and numerous others.